Investigação da presença de determinadas espécies bacterianas anaeróbias em dentes decíduos necrosados e avaliação de duas técnicas de instrumentação endodôntica em Odontopediatria - Gomes, Genara Brum (2011)
Maintaining the integrity and function of primary dentition is one of the main purposes of pediatric dentistry. Bacteria and their products are responsible for the development of endodontic pathologies in primary teeth. This study aimed to identify the presence of specific anaerobic bacteria in infected pulp chambers (PC) and root canals (RC) of necrotic primary teeth by the PCR method and to make an in vivo comparison of the effectiveness between two molar tooth endodontic instrumentation techniques manual and rotary with reference to the time instrumentation and the time to perform the filling. The study consisted in the microbial investigation of primary teeth with pulp necrosis of 15 patients. Samples were collected by using cotton balls (PC) and sterile absorbent paper points (RC). Bacterial DNA was extracted by means of DNA extraction kits. After DNA extraction, PCR reaction was performed through the use of specific primers to detect the occurrence of the following microorganisms: Filifactor alocis, Fusobacterium nucleatum, Parvimonas micra, Porphyromonas endodontalis, P. gingivalis, Prevotella intermedia, P. nigrescens, P. tannerae, Tanerella forsythia, Treponema denticola and T. socranskii. PCR products were analized by 1% agarose gel stained by red gel and viewed under ultraviolet transillumination. To compare instrumentation techniques, 8 patients (4 for each technique used) between 6 and 8 years of age were selected. Teeth were prepared by using n. 15 up to 30 K-type files for the manual technique; for the rotary technique, S2, F1 and F2 Pro Taper instruments were used. Filling was performed with iodoform-based paste. Instrumentation and filling duration were recorded. Collected data for each study were typed on Excel spreadsheets and analyzed statistically. A 5% significance level (P<0.05) was adopted for all tests. The results showed that the most frequently detected species were P. nigrescens (12/15), P. gingivalis (11/15) and F. alocis in the PC, and P. gingivalis (15/15) and P. nigrescens (14/15) in the RC. The red complex was not found in the PC, but was found in the RC in three cases. Only the simultaneous presence of P. nigrescens in the PC and in the RC was statistically associated (p=0.04). There were no significant statistical differences in instrumentation and filling duration between the techniques used, and differences in the quality of fillings were not observed. Thus, strict anaerobic bacteria were often detected in PC and RC samples. RC preparation with rotary instrumentation may be an alternative to manual instrumentation; however, it does not decrease the time of pediatric dentistry work in a significant way